Experimental investigation on the cyclic performance of perfobond rib shear connectors. Issue 16 (December 2020) - Li, Zhixiang; Wu, Bin; Liao, Man; Yang, Xingwang; Deng, Kailai; Zhao, Canhui
The behavior of perfobond rib shear connectors (PBL shear connectors) under monotonic loading has been widely studied. However, the performance of these connectors under cyclic loading is poorly understood and has seldom been investigated. This work presents an experimental study focusing on the cyclic performance of representative PBL shear connectors with passing rebar. Optical fibers were introduced to measure the detailed strain distributions. Results showed that the bearing capacity of these connectors could reduce up to 55.04% when compared with that under monotonic loading. The performance of these connectors differed significantly between the pull and push directions in the cyclic loading process. The concrete cracks, relative slip, and strains were developed earlier and more completely under pull than under push. Furthermore, rapid stiffness degradation, severe cracking and deformation of the concrete dowels were revealed, indicating the rapid failure of the adhesive effect, reduction of both the shear-friction effect and the dowel action of the passing rebars. These factors all contributed to the observed significant cyclic deterioration of the peak load and the slip. Based on this, a modified formula was proposed to consider the reduction effect. Comparisons between the analytical solution and test results validated the formula.